Performance of miniature piezocones in thinly layered soils - Hird, C; Johnson, P; Sills, G (2003)
Two piezocones, with cross-sectional areas of 1 cm2 and 5 cm2 and a variety of pore pressure filters, were driven at the standard rate 20 mm/s into models of thinly layered soil, and pore pressure dissipation tests were also performed. The models consisted of alternating layers of pre-consolidated kaolin clay and more permeable layers of silt or fine sand, enclosed in a 400 mm diameter cell with either a rigid or a flexible lateral boundary. Control tests were performed on a clay model without any sand or silt layers. The experiments demonstrate the feasibility of using miniature piezocones to detect individual permeable layers as thin as 2 mm in normally and lightly overconsolidated clay deposits, provided their vertical spacing is at least two cone diameters and a sufficiently fast data recording rate is used. However, the lateral extent of a permeable layer cannot be gauged from a single piezocone probe. Pore pressure dissipation tests in clay layers are not significantly affected by neighbouring permeable layers provided they are more than two cone diameters above or below the filter element. On the basis of the experimental results, it is suggested that miniature piezocones could be used to improve the investigation of thinly layered ground, as might be found in alluvial and estuarine areas.